Analogically Re-Imagining Post-Anselmian Soteriology with Lonergan and Balthasar - Ryliškytė, Ligita (Irish theological quarterly, 2025)
Responding to modern critiques that portray post-Anselmian soteriology as oppressive or blasphemous, this study reinterprets Christ’s satisfaction within Anselm’s ecclesial-monastic, rather than feudal, context. It examines Lonergan’s sacramental-penitential and Balthasar’s monastic-doxological interpretations of Christ’s satisfaction as complementary and mutually illuminating contributions toward analogically re-imagining a post-Anselmian soteriology. The essay culminates in proposing a synthetic analogy of ‘doxological conciliation’ that addresses contemporary concerns, clarifying its meaning in relation to Khaled Anatolios’s recently coined term, ‘doxological contrition.’